2001
DOI: 10.1007/pl00011210
|View full text |Cite
|
Sign up to set email alerts
|

Focal Eosinophilic Myositis

Abstract: Idiopathic hypereosinophilic syndrome (HES) is a heterogeneous group of disorders with the common features of prolonged eosinophilia of underdetermined cause and multiple organ system dysfunction. Focal eosinophilic myositis is an uncommon manifestation of HES. We report a case of focal eosinophilic myositis with tender muscle swelling followed by proximal weakness, but without non-systemic symptoms and muscle trophism in the lower limbs. Muscle biopsy specimen showed acute myositis with eosinophil infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…The lack of characteristic skin induration on examination suggested that he did not have eosinophilic fasciitis, and the history of absence of exposure to products containing L ‐tryptophan or intake of adulterated rapeseed oil excluded the diagnosis of eosinophilia–myalgia syndrome or toxic oil syndrome, the two syndromes implicating poisoning in an epidemic way that are rarely encountered nowadays. Clinically, the differential diagnosis (see Table 1) also included eosinophilic myositis and polymyositis,8, 9, 12 even though these were unlikely, given the relatively mild muscle weakness, absence of systemic involvement, normal serum CK levels, and normal electromyographic studies. The skin–fascia–muscle biopsy was the examination of choice to distinguish between the different entities; it demonstrated the absence of skin or fascial involvement but revealed a multifocal macrophagic and CD4 + T‐lymphocytic perimysial infiltration of muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of characteristic skin induration on examination suggested that he did not have eosinophilic fasciitis, and the history of absence of exposure to products containing L ‐tryptophan or intake of adulterated rapeseed oil excluded the diagnosis of eosinophilia–myalgia syndrome or toxic oil syndrome, the two syndromes implicating poisoning in an epidemic way that are rarely encountered nowadays. Clinically, the differential diagnosis (see Table 1) also included eosinophilic myositis and polymyositis,8, 9, 12 even though these were unlikely, given the relatively mild muscle weakness, absence of systemic involvement, normal serum CK levels, and normal electromyographic studies. The skin–fascia–muscle biopsy was the examination of choice to distinguish between the different entities; it demonstrated the absence of skin or fascial involvement but revealed a multifocal macrophagic and CD4 + T‐lymphocytic perimysial infiltration of muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Etiologies include parasitic infection, vasculitides (in particular, Churg–Strauss syndrome),4 nonhematological and hematological malignant diseases,3 idiopathic hypereosinophilic syndrome,3, 6 toxic oil syndrome,1 and L ‐tryptophan–induced eosinophilia–myalgia syndrome 7. Besides these recognized entities, a few others exist, of unknown etiology, including the well‐described eosinophilic fasciitis or Shulman syndrome,2, 12–14 in which inflammation primarily affects the deep fascia with skin induration and mild muscle involvement, and eosinophilic myositis and eosinophilic polymyositis,8, 12 in which deep eosinophilic infiltration of muscle is associated with muscle necrosis and increased serum creatine kinase (CK) levels. There is still another rare syndrome, wherein inflammatory cells are seen predominantly in the perimysium without significant endomysial infiltration or myonecrosis, and serum CK levels are usually normal 11, 12, 16.…”
mentioning
confidence: 99%
“…Despite both normal electrodiagnostic studies and CK levels, histopathologic studies revealed an inflammatory infiltrate consisting of eosinophils and other mononuclear cells in the perimysial connective tissue [9]. Kobayashi et al [10] reported a patient with eosinophilic myositis in which eosinophils infiltrate the endomysium. Their patient had electromyographic features typical of myositis as well as highly elevated serum CK [10].…”
Section: Inflammatory Myopathymentioning
confidence: 98%
“…Kobayashi et al [10] reported a patient with eosinophilic myositis in which eosinophils infiltrate the endomysium. Their patient had electromyographic features typical of myositis as well as highly elevated serum CK [10].…”
Section: Inflammatory Myopathymentioning
confidence: 98%
“…These criteria are based on the main clinical, laboratory, and histologic features that have been described in these diseases. [121][122][123][124][125][126][127][128][129] Box 5 Proposed diagnostic criteria for focal eosinophilic myositis, eosinophilic polymyositis, and eosinophilic perimyositis Proposed diagnostic criteria for focal eosinophilic myositis Deep vein thrombosis, cellulitis, and parasitic infections must be excluded to apply these criteria.…”
Section: Clinical Features and Diagnostic Investigationmentioning
confidence: 99%